Deep Tumor Penetrating Bioparticulates Inspired Burst Intracellular Drug Release for Precision Chemo‐Phototherapy. Issue 12 (10th January 2018) - Wang, Ruoning; Han, Yue; Sun, Bo; Zhao, Ziqiang; Opoku‐Damoah, Yaw; Cheng, Hao; Zhang, Huaqing; Zhou, Jianping; Ding, Yang
Abstract: The relevance of personalized medicine has inspired research for individually concerted diagnosis and therapy. Numerous efforts are devoted to designing drug particulates with capabilities of tumor penetrating and subcellular trafficking to concurrently discharge theranostics in response to multistimulations. In this study, a bioinspired particulate, formulated with whole components of native high‐density lipoproteins (HDLs) and decorated with the tumor‐penetrating peptide iRGD, is proposed to promote tumor penetration of HDLs (pHDLs) together with payloads. Specifically, paclitaxel (PTX), and the NIR fluorescent probe indocyanine green (ICG) are integrated into pHDLs (pHDL/PTX‐ICG) for synergetic chemo‐phototherapy. Inspired by lipoproteins, pHDLs are not only restored from naturally occurring materials but also possessed artificially endowed functions, leading to an enhanced cellular uptake, higher accumulation, and deep penetration into tumors without causing appreciable adverse effects, compared to reconstituted HDLs or lipid‐based nanoparticles. After intravenous administration, pHDL/PTX‐ICG performs a burst of intracellular drug release and imaging‐guided precision chemo‐phototherapy upon NIR irradiation that completely eradicates xenograft tumors. Neither recurrence nor significant toxicity is observed due to maneuvered regional photodynamic and photothermal therapy. Taken together, pHDL/PTX‐ICG is proven to be a promising platform to achieve deep tumor penetration and imaging‐guided chemo‐phototherapy. Abstract : In this study, a bioinspired particulate, formulated with whole‐components of native high‐density lipoproteins (HDLs) and decorated with the tumor‐penetrating peptide iRGD, is proposed to promote tumor penetration of HDLs (pHDLs) together with payloads. Specifically, paclitaxel (PTX), and the NIR fluorescent probe indocyanine green (ICG) are integrated into pHDLs (pHDL/PTX‐ICG) for synergetic chemo‐phototherapy.